Clean earth – clean sky: impact of locating bus stations on sustainable transportation sector in Malaysia - Shafaghat, Arezou (2008)

(untitled)
Our climate condition is changing and there is now scientific, social and political recognition that it is definitely a consequence of increasing anthropogenic greenhouse gas emission. Transport now allocates for about 20% of global anthropogenic carbon dioxide emission, and these amounts are progressing faster than for any other sector. However, access to sustainable transportation supports our current way of life; indeed, good mobility is a fundamental component of our desires. The transport sector in particular depends entirely on system implementation, fuel consumption and planning, which is divided to urban planning and urban design. Networking efficient and public transportation helps to control transport sector in terms of urban planning, on the other hand, urban design presents some guidelines, for instance, land use functions, green integrative space, urban furniture design, transit oriented and green design _non-polluter vehicles such as bicycle _ which have the potentials to provide benefits to the sustainable transportation. The global climate policy is going to supply clean and healthy air with less fuel consumption and greenhouse gas emission; in urban furniture design locating bus stations in cities is one of the particular subjects proves it, which makes possible for fossil carbon to remain in the soil, instead of ending up in the atmosphere by optimizing distances between stations linking two main places. The paper defines the sustainability on the basis of relevant subjects in the view of transportation; which are Greenhouses gas emission, Biodiversity, Environment, Prosperity and Social well-being. It intends to know how large could the locating bus stations play a role in sustainable transportation in Malaysia? Also, it aims to address this main question through critical review of the literature for exploring of key development strategies for suitable placement of bus stations in cities focusing particularly on transportation from public healthy and pollution aspects.